SPEED DETECTION METHODS IN VEHICULAR NAVIGATION - et al., Raj Shree (International Journal of Advanced Science and Technology, 2019)
Detecting the speed of a vehicle is very popular and challenging task in vision based computer applications. There are various methods available that uses to detect the speed of the vehicle but recent few years the sensor technologies such as RADAR or LIDAR are more actively using to detect the speed of the vehicle with very high precision. Most important thing to assure that the correct object is in the frame while detecting the speed of the vehicle because there would be certain obstacle also appears with object which can decrease the performance and accuracy of the system. Speed estimation plays a very crucial role in many areas, such as object and vehicle speed detection in transportation industry, object motion analysis in robot field, pedestrian behavior analysis in driverless vehicle area. In this paper we have discussed the various speed detection methods.